PEMBAHARUAN KURIKULUM DAYAH - Badruddin, Badruddin (Institut Daarul Qur'an Jakarta, Indonesia, 2021)
The research aims to analyze the reforms that have occurred in the Dayah Ma'hadad Ulumudiniyah Diniyah Islamiah Mesjid Raya in both the curriculum and learning aspects. This research uses Case Study. Data obtained through the field in Ma'hadad Ulumiyah Diniyah Islamiyah Mesjid Raya while secondary data will be found through reading materials that are in books to support the primary data. The type of research in terms of analysis is a qualitative-descriptive research. It is mentioned that this qualitative research is because in this study it does not use numbers, it will be more in the form of a narrative. The data collection that the researchers did in this research through three stages, namely participant observation involved observation, interview and documentation. The results showed that there had been changes in the Dayah Ma'hadad Ulumudiniyah Diniyah Islamiah Mesjid Raya curriculum. This renewal is due to the guidance of the times and the preparation of a generation that is superior and able to compete with graduates of other educational institutions.